Preface 3(1) March 2024 - Warji, Warji (abe.fp.unila.ac.id, 2024)
Editorial Introduction By giving thanks to Allah the Almighty, the Journal of Agricultural Biosystem Engineering (J-ABE) Volume 3 No 1, March 2024 can be published. This edition contains 15 (Fifteen) articles which are scientific papers from various fields of study in the world of Agricultural Engineering which includeing cultivating, waste processing, mapping, renewable energy, design, and bioprocess technology.On this occasion, we would like to express our deepest gratitude to the authors for their contributions to J-ABE and to the reviewers of this journal for their participation in improving the quality of scientific papers published in this edition.In conclusion, we hope that this J-ABE will benefit society and make a meaningful contribution to the development of science and technology, especially in the field of agricultural engineering. Editor of J-ABE